2021
DOI: 10.1097/jps.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner-Managed Clinic Reduces Emergency Department Visits for Parents of Children With Problematic Gastrostomy Tubes

Abstract: Background Gastrostomy tube (G-tube) placement is commonly performed on pediatric patients but has high rates of emergency department (ED) utilization. We hypothesized that a nurse-practitioner-driven G-tube clinic would reduce ED visits and complications and improve provider and patient satisfaction. Methods After institutional review board approval, a retrospective chart review was conducted for all patients < 18 years old undergoing G-tube placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Traditionally, it is thought the problem of ED overcrowding is the fault of the ED itselfstaff shortage, lack of space, incompetence in patient throughput, and so forth-but in reality, the problem of ED overcrowding is much larger than one department and is, indeed, a health care issue where all aspects of the medical institution are involved (Jeanmonod, 2018). Prior research has shown that including interdisciplinary care, including nurse-practitioner-led clinics, can reduce ED utilization (Maselli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, it is thought the problem of ED overcrowding is the fault of the ED itselfstaff shortage, lack of space, incompetence in patient throughput, and so forth-but in reality, the problem of ED overcrowding is much larger than one department and is, indeed, a health care issue where all aspects of the medical institution are involved (Jeanmonod, 2018). Prior research has shown that including interdisciplinary care, including nurse-practitioner-led clinics, can reduce ED utilization (Maselli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%